2003
DOI: 10.5194/acp-3-1871-2003
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous (DMS, MSA, SO<sub>2</sub>, H<sub>2</sub>SO<sub>4</sub> and DMSO) and particulate (sulfate and methanesulfonate) sulfur species over the northeastern coast of Crete

Abstract: Abstract.A detailed study of the levels, the temporal and diurnal variability of the main compounds involved in the biogenic sulfur cycle was carried out in Crete (Eastern Mediterranean) Dimethylsulfide (DMS) levels ranged from 2.9 to 136 pmol·mol −1 (mean value of 21.7 pmol·mol −1 ) and showed a clear diurnal variation with daytime maximum. During nighttime DMS levels fall close or below the detection limit of 2 pmol·mol −1 . Concurrent measurements of OH and NO 3 radicals during the campaign indicate that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 58 publications
5
79
1
5
Order By: Relevance
“…A H 2 SO 4 mixing ratio of 80 pptv seems to be too high for all trajectories since no data points are found in the gray shaded area. This is in agreement with measurements of gaseous H 2 SO 4 which even in polluted areas showed mixing ratios lower than 80 pptv (Bardouki et al, 2003;Berresheim et al, 2002). A better comparison with the measurements can be derived when only the trajectories that were started near the location where the flights were performed are considered (Fig.…”
Section: Comparison With Measurementssupporting
confidence: 78%
See 1 more Smart Citation
“…A H 2 SO 4 mixing ratio of 80 pptv seems to be too high for all trajectories since no data points are found in the gray shaded area. This is in agreement with measurements of gaseous H 2 SO 4 which even in polluted areas showed mixing ratios lower than 80 pptv (Bardouki et al, 2003;Berresheim et al, 2002). A better comparison with the measurements can be derived when only the trajectories that were started near the location where the flights were performed are considered (Fig.…”
Section: Comparison With Measurementssupporting
confidence: 78%
“…Gas phase sulfuric acid concentrations are typically much lower and range between 10 5 to 10 7 molecules cm −3 in clean air (e.g. Eisele and Tanner, 1993) and up to 10 8 molecules cm −3 for polluted air (Berresheim et al, 2002;Bardouki et al, 2003). The simulations were performed along the 36 trajectories for three different gas phase sulfuric acid mixing ratios µ H 2 SO 4 =1, 40 and 80 pptv (1 pptv=2.67×10 7 molecules cm −3 at 0 • C and 1013 hPa), where a mixing ratio of µ H 2 SO 4 =1 pptv is representative for clean air and mixing ratios of µ H 2 SO 4 =40 and 80 pptv are representative for polluted air.…”
Section: Box Model Simulationsmentioning
confidence: 99%
“…In turn, As, Cd and Pb, identified as elements that can cause carcinogenic health effects (Behera et al, 2015), were also found predominantly in the PM 2.5 (over 75 %). In this way, they may be indicative of higher carcinogenicity of fine over coarse particles.…”
Section: Biomass Burning Tracersmentioning
confidence: 99%
“…It is noteworthy that MSA was associated with NW winds. This species is often associated with the decomposition of DMS emitted by the sea (Bardouki et al, 2003). More studies are needed in order to identify MSA sources at this site.…”
Section: Source Apportionment Using Pmf and Polar Plotsmentioning
confidence: 99%
“…In general, sulfate concentrations started to increase very rapidly around noon and reached their diurnal maximum during the afternoon, after which they decreased first gradually and then more rapidly until the following noon. The afternoon increase in the sulfate concentration can be ascribed to the intensive photochemical production of gaseous sulfuric acid from both natural and anthropogenic precursors during daytime, followed by the condensation of sulfuric acid into preexisting aerosol particles together with gaseous ammonia (e.g., Zerefos et al, 2000;Kouvarakis and Mihalopoulos, 2002;Bardouki et al, 2003;Mihalopoulos et al, 2007). Since sulfate is practically non-volatile, the decreasing sulfate concentrations during night and morning hours are most likely a combination of air mass dilution by entrainment and aerosol deposition processes.…”
Section: Aerosol Chemical Composition Hygroscopicity and Ccn Activitymentioning
confidence: 99%